MODERN METHODS OF COMMUNICATIVE ENGLISH TEACHING - Abdisattarova Marjona Sherzod qizi, (TADQIQOTLAR, 2025)
Abstract This  article  explores  the  importance  of  modern  communicative  methods  in teaching  English,  their  effectiveness  in  the  learning  process,  and  their  role  in developing students’ language skills. It also examines interactive approaches such as role play, brainstorming, case study, and debate, and discusses their impact on students’ communication skills and motivation.